An Important Aspect of Performance management for Managing the Efficiency of Employees in an Organization - Jermsittiparsert, Kittisak; Thanh Nguyen, Phong; Thuy To Nguyen, Quyen Le Hoang; Bich Huynh, Vy Dang (Opción, 2019)
Between an employee and a supervisor an ongoing communication process that develop for supporting of accomplishing the defined target of an organ- ization is known as performance management. The process of communica- tion include providing feedback, clarifying expectations, reviewing results, identifying goals and setting objectives. The performance management sys- tem also measures the performance of an employee in an organization. For managing the efficiency of an employee is continually review and monitor the work of the employee.